Determinant factors of early marriage in developing countries: a literature review - Dhonna Anggreni; Hari B. Notobroto; Oedojo Soedirham (Journal of Public Health in Africa, 2023)
Introduction: Early marriage is carried out before the teenager is even 18 years old. It is estimated that around 650 million teenagers in the world are married before they are 18 years old. Early marriage does not only have an impact on adolescent health, but globally will also affect national security, social development, human rights, economic development, and gender equality.